2022
DOI: 10.1111/ejn.15791
|View full text |Cite
|
Sign up to set email alerts
|

In silico gene expression and pathway analysis of DEK in the human brain across the lifespan

Abstract: DEK, a chromatin-remodelling phosphoprotein, is associated with various functions and biological pathways in the periphery, including inflammation, oncogenesis, DNA repair, and transcriptional regulation. We recently identified an association between DEK loss and central nervous system diseases, such as Alzheimer's. To understand DEK's potential role in disease, it is critical to characterize DEK in healthy human brain to distinguish between neural DEK expression and function in healthy versus diseased states … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…We observed sex differences in DEK expression in the demented human brain but not in the healthy brain (O'Donovan et al, 2018;Greene et al, 2022). DEK is known to be a target gene of sex hormone receptors (Privette Vinnedge et al, 2012), and hormone regulation and signaling have been identified as DEK-associated pathways in the human brain (Greene et al, 2022). Therefore, it will be important to consider the potential sex-specific effect of DEK loss in AD and other age-related dementias.…”
Section: Future Directionsmentioning
confidence: 85%
See 4 more Smart Citations
“…We observed sex differences in DEK expression in the demented human brain but not in the healthy brain (O'Donovan et al, 2018;Greene et al, 2022). DEK is known to be a target gene of sex hormone receptors (Privette Vinnedge et al, 2012), and hormone regulation and signaling have been identified as DEK-associated pathways in the human brain (Greene et al, 2022). Therefore, it will be important to consider the potential sex-specific effect of DEK loss in AD and other age-related dementias.…”
Section: Future Directionsmentioning
confidence: 85%
“…First, we do not know how DEK loss could impact neurodegeneration differently in males and females. We observed sex differences in DEK expression in the demented human brain but not in the healthy brain (O'Donovan et al, 2018;Greene et al, 2022). DEK is known to be a target gene of sex hormone receptors (Privette Vinnedge et al, 2012), and hormone regulation and signaling have been identified as DEK-associated pathways in the human brain (Greene et al, 2022).…”
Section: Future Directionsmentioning
confidence: 90%
See 3 more Smart Citations